Advancing the equality and diversity agenda in armed forces: global perspectives. Issue 7 (7th October 2014) - Ishaq, Mohammed; Maaria Hussain, Asifa
Abstract : Purpose: – Focusing on some of the key strands of equality and diversity (E&D), the purpose of this paper is to highlight the progress made by armed forces in implementing the E&D agenda, with specific focus on Anglophone countries and their allies. The research also looks at the obstacles encountered by managers and policymakers in attempting to establish effective diversity management in a traditionally highly conservative public sector institution. Design/methodology/approach: – Using an approach known as secondary analysis, there is an in-depth review of a wide range of data sources. Findings: – The analysis reveals that E&D issues in armed forces have been under researched and there is also unbalanced coverage and reporting of E&D across nations. There is also evidence of greater progress on diversity management in the armed forces of some countries but a distinct lack of progress in others. A combination of political, legal, economic and social influences are impinging on the culture of militaries. Whilst in the long-term these pressures are likely to result in armed forces becoming more reflective of developments in wider society, the road to achieving this is still fraught with uncertainty. Originality/value: – To increase the understanding of diversity management in public institutions characterised by an mono culture and traditionally associated with resistance to change, and establish the extent to which the legal, social justice and business cases for promoting E&D are wholly applicable to the armed forces.